2006
DOI: 10.1144/gsl.mem.2006.032.01.35
|View full text |Cite
|
Sign up to set email alerts
|

The Lapland-Kola orogen: Palaeoproterozoic collision and accretion of the northern Fennoscandian lithosphere

Abstract: A tectonic model is proposed for the Palaeoproterozoic Lapland-Kola orogen (LKO) in the northern Fennoscandian Shield. Although long regarded as an Archaean craton, integrated geological, geochemical and geophysical observations show that the Lapland-Kola orogen is a Palaeoproterozoic collisional belt containing both Archaean terranes and an important component of juvenile Palaeoproterozoic crust. Rifting, from 2.5 to 2.1 Ga, began under the influence of a mantle plume (> 1000 km diameter), related to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
137
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(152 citation statements)
references
References 47 publications
3
137
0
12
Order By: Relevance
“…4, the Karelia position was constrained by the 1984 Ma Pudozhgora Intrusion pole (Lubnina et al 2016), and Kola Craton is tentatively positioned close to Karelia. According to Daly et al (2006), after the formation of the Archean Kernoland supercontinent (Pesonen et al 2003), a Wilson cycle was developed between Kola and Karelia after the break-up of this supercontinent at ca. 2500 Ma.…”
Section: The Proto-amazonian Craton Before Columbiamentioning
confidence: 99%
“…4, the Karelia position was constrained by the 1984 Ma Pudozhgora Intrusion pole (Lubnina et al 2016), and Kola Craton is tentatively positioned close to Karelia. According to Daly et al (2006), after the formation of the Archean Kernoland supercontinent (Pesonen et al 2003), a Wilson cycle was developed between Kola and Karelia after the break-up of this supercontinent at ca. 2500 Ma.…”
Section: The Proto-amazonian Craton Before Columbiamentioning
confidence: 99%
“…1) has shown that: Both belts were formed by the superposition of two Precambrian orogenies. The earth crust of the Belomorian belt was produced during the Mesoarchaean to Neoarchaean Belomorian collisional orogeny [Slabunov, 2008;Slabunov et al, 2006] and then was reworked during the Palaeoproterozoic Lapland-Kola collisional orogeny [Daly at al., 2006;Balagansky et al, 2014]. The earth crust of the Trans-North China orogen was formed during a Neoarchean accretionary orogeny and then was reworked during a Paleoproterozoic collisional orogeny [Zhao et al, 2012;Guo et al, 2012Guo et al, , 2005.…”
mentioning
confidence: 99%
“…2) with its magmatic arctype granodiorites, diorites and gabbros that have yielded Neoarchaean zircon ages in the east/northeast and Palaeoproterozoic ages in the west/southwest (Meriläinen, 1976;Lehtinen et al, 2005;Daly et al, 2006). Subordinate metasupracrustal rocks have also been reported in this terrane.…”
Section: Resultsmentioning
confidence: 93%
“…In general, there is a basic two-fold division into the Caledonides sensu stricto and a mid-crustal continental lithospheric basement comprising autochthonous crystalline com plexes that range in age from Neoarchaean to Late Palaeo proterozoic and form the northern margin of the Fennoscandian Shield ( Fig. 1; Gaál et al, 1989;Daly et al, 2006). These older Precambrian rocks occur mainly in eastern Finnmark and western Troms, and some are either affected locally by Caledonian deformation or incorporated as thrust slices in the Caledonian nappes (Fig.…”
Section: Geology Of Finnmark and North Tromsmentioning
confidence: 99%
See 1 more Smart Citation